Steroids from the aerial parts of Leonurus japonicus. (June 2015) - Zhou, Qin-mei; Peng, Cheng; Yang, Huai; Liu, Lu-si; Yang, Yu-ting; Xie, Xiao-fang; Guo, Li; Liu, Zhao-hua; Xiong, Liang
Graphical abstract: Highlights: Two new and ten known steroids were isolated from Leonurus japonicus . The structure of 1 was confirmed by single crystal X-ray crystallographic analysis. Compound 2 was characterized by esterification of β-sitosterol with an aliphatic diacid. The isolates were assayed for anti-platelet aggregation activity and cytotoxic activity. Abstract: Two new steroids, (24 S )-stigmast-4, 28-diene-24-ol-3-one (1 ) and mono-β-sitosteryl azelate (2 ), along with ten known analogues (3 –12 ), were isolated from the ethanolic extract of Leonurus japonicus Houtt. Their structures were elucidated by spectroscopic and chemical methods. The absolute configuration of 1 was confirmed by single crystal X-ray crystallographic analysis using anomalous scattering of Cu Kα radiation. Compounds 3, 4, and 9 showed significant inhibitory activities against ADP-induced platelet aggregation, while compound 1 had a weak cytotoxic activity against acute myeloid leukemia cell line MV4-11.